2015
DOI: 10.1002/hed.23868
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for and occurrence of postoperative cervical hematoma after thyroid surgery: A single-institution study based on 5156 cases from the past 2 years

Abstract: Hematoma often occurs within 12 hours after thyroid surgery. Hypertension, previous thyroid surgery, male sex, and benign pathology may increase the risk of hematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 10 publications
(26 reference statements)
6
35
1
1
Order By: Relevance
“…Flow chart of the meta-analysis. (2,4,6,11,12,17). After the analysis, we concluded that the use of antithrombotic agents for thyroidectomy patients, regardless of dosage, was associated with post-thyroidectomy haemorrhage (OR = 1.96, 95% CI = 1.55-2.49, P < 0.00001) ( Fig.…”
Section: Figurementioning
confidence: 87%
See 2 more Smart Citations
“…Flow chart of the meta-analysis. (2,4,6,11,12,17). After the analysis, we concluded that the use of antithrombotic agents for thyroidectomy patients, regardless of dosage, was associated with post-thyroidectomy haemorrhage (OR = 1.96, 95% CI = 1.55-2.49, P < 0.00001) ( Fig.…”
Section: Figurementioning
confidence: 87%
“…We used a fixed-effects model to analyse the data involving the use of a drainage device (I 2 = 0%, P = 0.49). In this analysis, 4 retrospective studies were included (3,8,12,26), and studies with selected conditions for drainage device use were excluded. The analysis showed that postthyroidectomy haemorrhage was not associated with the use of a drainage device (OR = 1.27, 95% CI = 0.74-2.18, P = 0.40) ( Fig.…”
Section: Drainage Device Usementioning
confidence: 99%
See 1 more Smart Citation
“…While some advocate for routine same-day surgery, others are more cautious, preferring to be more selective for same-day surgery cases and requiring a period of observation before dismissal. 6,9,18,23,24 Recommended time periods of observation vary and also differ with procedure (lobectomy vs. total). 4,6,9,18,24 Recommendations are based on the observations within large, retrospective studies and the timing of POH formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how additional variables thought to also influence the development of POH may interact and influence POH rates. 10,24 …”
Section: Discussionmentioning
confidence: 99%